Integration of IOT and AI for Next Generation Smart Homes - Gavali, Pratik Chandrashekhar; Shirbhate, Arjun Manojkumar (Journal of Advanced Research in Applied Artificial Intelligence and Neural Network; Vol 9 No 2 (2025): Journal of Advanced Research in Applied Artificial Intelligence and Neural Network, 2025)
Sentient Spaces is an innovative system designed to integrate various smart technologies to enhance convenience, efficiency, and security of home environments. Leveraging IoT devices, real-time data processing, and machine learning algorithms, Smart Home offers a comprehensive solution for modern living. This paper outlines the system’s architecture, key features, and future enhancements, showcasing its potential to transform residential living.